Association of physician payment model and team-based care with timely access in primary care: a population-based cross-sectional study - Kiran, Tara; Green, Michael E.; DeWit, Yvonne; Khan, Shahriar; Schultz, Sue; Kopp, Alexander; Yeritsyan, Naira; Wissam, Haj Ali; Glazier, Richard H. (CMAJ Open, 2020)
Background: It is unclear how patient-reported access to primary care differs by physician payment model and participation in team-based care. We examined the association between timely and after-hours access to primary care and physician payment model and participation in team-based care, and sought to assess how access varied by patient characteristics.Methods: We conducted a cross-sectional analysis of adult (age ≥ 16 yr) Ontarians who responded to the Ontario Health Care Experience Survey between January 2013 and September 2015, reported having a primary care provider and agreed to have their responses linked to health administrative data. Access measures included the proportion of respondents who reported same-day or next-day access when sick, satisfaction with time to appointment when sick, telephone access and knowledge of an after-hours clinic. We tested the association between practice model and measures of access using logistic regression after stratifying for rurality.Results: A total of 33 665 respondents met our inclusion criteria. In big cities, respondents in team and nonteam capitation models were less likely to report same-day or next-day access when sick than respondents in enhanced fee-for-service models (team capitation 43%, adjusted odds ratio [OR] 0.88, 95% confidence interval [CI] 0.79–0.98; nonteam capitation 39%, adjusted OR 0.78, 95% CI 0.70–0.87; enhanced fee-for-service 46% [reference]). Respondents in team and nonteam capitation models were more likely than those in enhanced fee-for-service models to report that their provider had an after-hours clinic (team capitation 59%, adjusted OR 2.59, 95% CI 2.39–2.81; nonteam capitation 51%, adjusted OR 1.90, 95% CI 1.76–2.04; enhanced fee-for service 34% [reference]). Patterns were similar for respondents in small towns. There was minimal to no difference by model for satisfaction with time to appointment or telephone access.Interpretation: In our setting, there was an association between some types of access to primary care and physician payment model and team-based care, but the direction was not consistent. Different measures of timely access are needed to understand health care system performance.